2006
DOI: 10.1183/09031936.06.00105505
|View full text |Cite
|
Sign up to set email alerts
|

A single-season prospective study of respiratory viral infections in lung transplant recipients

Abstract: The frequency and complications of respiratory viral infections (RVI) were studied in 50 ambulatory lung transplant patients during a single winter season, using viral antigens, viral cultures and PCR of nasal washes or bronchoalveolar lavages. Patients' survival, episodes of acute rejection and occurrence of bronchiolitis obliterans (BO) or BO syndrome (BOS) were monitored for 1 yr after the study.Overall, 32 (64%) patients had 49 symptomatic episodes. Documented infections included eight due to respiratory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 22 publications
2
88
1
2
Order By: Relevance
“…34 Some epidemiologic studies have suggested an association between respiratory viral infection and the development of bronchiolitis obliterans syndrome (BOS). [35][36][37][38][39][40] These studies yielded mixed results and the association between respiratory virus infection and BOS remains unclear. 41,42 The recent availability of molecular diagnostics, including PCR and multiplex gene techniques for the recovery of many viruses simultaneously from a single specimen, increased the recovery of pathogens in respiratory infections that previously were considered to be of undetermined etiology.…”
Section: Respiratory Viral Infectionsmentioning
confidence: 93%
“…34 Some epidemiologic studies have suggested an association between respiratory viral infection and the development of bronchiolitis obliterans syndrome (BOS). [35][36][37][38][39][40] These studies yielded mixed results and the association between respiratory virus infection and BOS remains unclear. 41,42 The recent availability of molecular diagnostics, including PCR and multiplex gene techniques for the recovery of many viruses simultaneously from a single specimen, increased the recovery of pathogens in respiratory infections that previously were considered to be of undetermined etiology.…”
Section: Respiratory Viral Infectionsmentioning
confidence: 93%
“…[1][2][3][4] RSV, a single-stranded, negativesense RNA virus, is a significant contributor to severe lower respiratory tract infections in lung transplant recipients. [5][6][7] Although the supportive care of patients with viral respiratory infections continues to improve, mortality rates of RSV infection in this population remain at 10% to 20%. 8 Early anti-viral therapy with ribavirin may be effective in RSV-infected patients not only after lung transplantation but also in other immunocompromised patient populations.…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative incidence of RSV infection in lung transplant over 5-7 years has varied from 8 to 21 % in several retrospective series, with an annual incidence describe of 2-16 % [57][58][59][60][61][62][63][64]. Mortality attributable to LRD with RSV in this population has been reported from 10 to 20 % [57,60].…”
Section: Sot Clinical Disease and Epidemiologymentioning
confidence: 98%